One-year antibody durability induced by EuCorVac-19, a liposome-displayed COVID-19 receptor binding domain subunit vaccine, in healthy Korean subjects - Lovell, Jonathan F.; Miura, Kazutoyo; Baik, Yeong Ok; Lee, Chankyu; Lee, Jeong-Yoon; Park, Young-Shin; Hong, Ingi; Lee, Jung Hyuk; Kim, Taewoo; Seo, Sang Hwan; Kim, Jae-Ouk; Song, Manki; et al. (International Journal of Infectious Diseases, 2024)
•EuCorVac-19 is a vaccine that displays the SARS-CoV-2 receptor binding domain on immunogenic liposomes.•As part of a Phase 2 trial, antibodies were tested 6 and 12 months after vaccination.•Median antibody half-life was 52 days in the early period, and 130 days in the late period.•Median neutralizing half-life was 120 days in the early period, and 214 days in the late period.•Antibody half-life was correlated to the magnitude of antibody response. EuCorVac-19 (ECV-19), an adjuvanted liposome-displayed receptor binding domain (RBD) COVID-19 vaccine, previously reported interim Phase 2 trial results showing induction of neutralizing antibodies 3 weeks after prime-boost immunization. The objective of this study was to determine the longer-term antibody response of the vaccine. To assess immunogenicity 6 and 12 months after vaccination, participants in the Phase 2 trial (NCT04783311) were excluded if they: 1) withdrew, 2) reported COVID-19 infection or additional vaccination, or 3) exhibited increasing Spike (S) antibodies (representing possible non-reported infection). Following exclusions, of the 197 initial subjects, anti-S IgG antibodies and neutralizing antibodies were further assessed in 124 subjects at the 6-month timepoint, and 36 subjects at the 12-month timepoint. Median anti-S antibody half-life was 52 days (interquartile range [IQR]:42-70), in the “early” period from 3 weeks to 6 months, and 130 days (IQR:97-169) in the “late” period from 6 to 12 months. There was a negative correlation between initial antibody titer and half-life. Anti-S and neutralizing antibody responses were correlated. Neutralizing antibody responses showed longer half-lives; the early period had a median half-life of 120 days (IQR:81-207), and the late period had a median half-life of 214 days (IQR:140-550). These data establish antibody durability of ECV-19, using a framework to analyze COVID-19 vaccine-induced antibodies during periods of high infection.